Parenteral Nutrition in Pediatric Patients with Neurodisability: Current Perspectives - White E; Mutalib M (Dove Medical Press, 2023)
Emily White,1 Mohamed Mutalib1,2 1Department of Paediatric Gastroenterology, Evelina London Children' Hospital, London, UK; 2Faculty of Life Sciences and Medicine, King's College London, London, UKCorrespondence: Mohamed Mutalib, Department of Paediatric Gastroenterology, Evelina London Children' Hospital, London, SE1 7EH, UK, Email Mohamed.mutalib@gstt.nhs.ukAbstract: Pediatric neurodisability describes functional limitations in children with varied severity and complexity often attributed to brain or neuromuscular abnormalities. The life expectancy of children with neurodisability is improving, but many will require significant medical support. The gastrointestinal tract is usually affected in children with neurodisability and can lead to a wide range of symptoms. In gastrointestinal (GI) dystonia, a newly coined term, feeding will trigger a distressing dystonia and symptoms can improve with cessation of feed. Parenteral nutrition (PN) is often viewed as a viable option in severe GI dystonia or when enteral feeding does not support sufficient nutrition. The use of PN in children with severe neurodisability is complex. It involves an intricate interplay between medical, psychological and ethical factors. In the absence of a universally agreed guidance on the use of PN in this cohort, paediatricians should maintain the individual need of the child at the centre of the decision-making process and work closely with families and other healthcare professionals before initiating or withholding PN in children with severe neurodisability. In this article, we discuss the complex and multifaceted approach to the use of PN in children with severe neurodisability and aimed to explore the medical, psychological and ethical aspect dilemmas facing clinicians looking after children with declining gut function who may require PN support.Keywords: pediatric, neurodisability, parenteral nutrition, medical ethics